CLIC1 and CLIC4 demonstrate cell protective antioxidant activity against UV exposure - Hossain, Khondker Rufaka; Alghalayini, Amani; Turkewitz, Daniel R.; Valenzuela, Stella M. (Frontiers in Cell and Developmental Biology, 2025)
BackgroundRedox homeostasis is critical for maintaining healthy biological systems. Under physiological conditions, the human antioxidant defence system relies on enzymes such as superoxide dismutase (SOD), catalase (CAT), and glutathione peroxidase (GPx). Recent studies have shown that members of the Chloride Intracellular Ion Channel (CLIC) protein family, particularly CLIC1 and CLIC4, also exhibit antioxidant and cytoprotective activities. Overexpression of these proteins confers cellular protection, whereas their knockdown increases susceptibility to oxidative stress.MethodsThis in vitro study investigated the antioxidant and cellular protective effects of CLIC1 and CLIC4 against UV-induced damage in human skin cells. Comparative analyses were performed using known endogenous antioxidant proteins, glutaredoxin (Grx) and Glutathione S-transferase-Omega (GST-Ω), as well as the antioxidant drug N-acetylcysteine (NAC). Recombinant purified CLIC proteins (rCLIC1 and rCLIC4) were added exogenously to skin cells, while CLIC knockdown models were used to assess loss-of-function effects.Results and DiscussionExogenous addition of rCLIC1 and rCLIC4 provided significant cellular protection against UV-induced oxidative damage, reducing reactive oxygen species (ROS) production. In contrast, knockdown of CLIC1 or CLIC4 increased cellular vulnerability to oxidative stress. The protective and antioxidant activities of rCLIC1 and rCLIC4 were comparable to those of Grx, GST-Ω, and NAC. These findings highlight the potent antioxidant and cytoprotective roles of CLIC1 and CLIC4 in maintaining cellular redox balance. The ability of exogenously added recombinant CLIC proteins to mitigate oxidative and UV-induced damage suggests potential therapeutic applications for this protein family in oxidative stress-related conditions.